Improving the Electrochemical Performances of LiVPO4F/C Cathode by Doping AlF3 with Dual Functions for Lithium Ion Batteries. Issue 10 (22nd August 2018) - Wen, Zheng; Li, Qiyuan; Fan, Changling; Luo, Ting; Zeng, Taotao; Han, Shaochang
Abstract: The performances of pure phase LiVPO4 F/C is poor. AlF3 is selected to dope it, which is synthesized by a novel chemical reduction. Alveolate structure is discovered in undoped sample because of the volatilization of fluoride. The selected area electron diffraction proves that it is composed of Li3 V2 (PO4 )3 and LiVPO4 F. However, the alveolate disappears in doped sample with pure parallelogram pattern because AlF3 supplements the loss of fluorine. Doping of Al 3+ decreases the lattice parameters and stabilizes the crystallite. Therefore, the performances of LiV1‐x Alx PO4 F/C at different temperatures are significantly improved. LiV0.97 Al0.03 PO4 F/C delivers high capacity of 116.6 mAh g −1 and excellent capacity retention of 96.83 % at 5 C after 50 cycles. The 5 C capacities at −10 °C and 55 °C are 90.1 mAh g −1 and 121.4 mAh g −1 . Ex‐situ X‐ray diffraction reveals that the lattice of LiV0.97 Al0.03 PO4 F/C can maintain stability after extreme testing conditions. These are ascribed to the improvement in intrinsic conductivity and diffuse coefficient. It implies that AlF3 plays dual functions in the doping process. Abstract : The fluoride in LiVPO4 F/C is unstable and it will volatilize in the synthesis process. This results in the formation of alveolate structure containing impurity Li3 V2 (PO4 )3 in undoped sample. However, when it is doped with AlF3, the alveolate structure disappears and pure phase LiVPO4 F/C is formed. This is because the greater partial pressure of fluorine around the precursor and the excessive of fluoride inhibit the evaporation of fluorine.